Performance ratio – Crucial parameter for grid connected PV plants. (November 2016) - Khalid, Ahmad Mohd; Mitra, Indradip; Warmuth, Werner; Schacht, Volker
Abstract: Performance Ratio (PR) is a globally accepted indicator to judge the performance of grid connected PV Plants. There are good examples from countries like the US, Australia and those in the European Union who have used PR as a key performance indicator to judge the performance of their PV systems. Such an analysis has helped these countries in continuously increasing the performance of their plants by rectifying system faults and thus plan for better investment decisions. The main focus of the paper is to highlight the importance of PR as a crucial performance indicator citing literature and research progress. In literature review, mainly, we discuss and compare few internationally acclaimed PV monitoring standards, guidelines, expert works and company methodologies, as to how they calculate the PR of a grid connected PV plant. Important issues over the definition of PR have also been discussed briefly. Later, arguments have been presented to support our claim of sticking to a bare minimum PR approach as defined by IEC 61724. This could significantly help countries in ramping up their grid PV capacities in the initial stages of development. At the end we have also highlighted economic and environmental benefits of using PR as a performance indicator by illustration of a case example from the SolMap project in India.